2008
DOI: 10.3390/ijms9020145
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Effect of Hypericin on the Conformation and Catalytic Activity of Hemoglobin

Abstract: Hypericin, extracted from H. perforatum, can induce the generation of reactive oxygen species by visible light irradiation, which may consequently induce the conformational change of hemoglobin. We have not only employed UV-vis spectroscopy to observe the changes of UV-vis spectra of the protein, which reveals the conformational changes of the protein, but also employed electrochemical method to obtain its enhanced peroxidase activity. The photodynamic effect of hypericin on the conformation and catalytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The process depends not only on the irradiation time but also on the concentration of hypericin. This study not only confirmed the photosensitization by hypericin and revealed the enhanced peroxidase activity of hemoglobin but may also find application in the development of a more sensitive H 2 O 2 biosensor using this molecule (Zhao et al, 2008).…”
Section: Naphthodianthronesmentioning
confidence: 51%
“…The process depends not only on the irradiation time but also on the concentration of hypericin. This study not only confirmed the photosensitization by hypericin and revealed the enhanced peroxidase activity of hemoglobin but may also find application in the development of a more sensitive H 2 O 2 biosensor using this molecule (Zhao et al, 2008).…”
Section: Naphthodianthronesmentioning
confidence: 51%
“…This second pathway is the so-called photodynamic effect. In particular, ROS induces structural changes of hemoglobin [17] , [18] and participates in the degradation process [19] , [20] . In a further series of experiments we therefore targeted to test for involvement of ROS in the observed UVI-induced fluorescence enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hypericin (HY), a phenanthroperylene quinine derivative, which is a widely used medicine for the treatment of depression, could induce the generation of ROS by visible light irradiation [121]. Therefore, irradiation on the surface of Hb and HY comodified electrode has been conducted and enhanced peroxidase activity of the protein has been obtained [122]. It is noteworthy that long time and strong irradiation need to be avoided, as more ROS than expected would interact with the amino acid residues of the protein and intensively damage the structure and activity of the protein.…”
Section: Activity Regulation Of Redox Proteinsmentioning
confidence: 99%